The potential of ethanolic extract of Moringa oleifera leaves on HSF1 expression in oral cancer induced by benzo[a]pyrene - Vania Syahputri; Theresia Indah Budhy; Bambang Sumaryono (Dental Journal (Majalah Kedokteran Gigi), 2020)
Background: Oral cancer is the sixth most common malignancy that occurs in the world, with more than 330,000 deaths a year. In cancer, mutations occur in proteins, accompanied by unfolding proteins, caused by the unstable micro-environment in cells. To stabilise this condition, protein protectors called heat shock proteins (HSPs) are needed. HSPs are activated by a group of transcription factors known as heat shock factor 1 (HSF1). HSF1 is a considered target in cancer therapy. Moringa oleifera leaves are known to have anti-cancer properties because of bioactive compounds called flavonoid and isothiocyanate and are used as herbal therapy for cancer. Purpose: To investigate the potential effect of ethanolic extract of Moringa oleifera on HSF1 expression in oral cancer induced by benzo[a]pyrene. Methods: This study used 25 male Wistar rats divided into five groups consisting of the negative control group (K-), which was only given aquadest; the positive control group (K+), which was induced with benzo[a]pyrene and given aquadest; and treatment groups that were induced with benzo[a]pyrene and given Moringa oleifera leaf extract at concentrations of 3.125% (P1), 6.25% (P2), and 9.375% (P3). Examination of HSF1 expression was carried out by immunohistochemistry staining. Data were analysed using the Kruskal–Wallis test and post-hoc Tukey HSD. Results: HSF1 expression in the P1, P2, and P3 groups decreased significantly compared to the K+ group. There were no significant differences between the P1, P2, and P3 groups (p > 0.005). Conclusion: Ethanolic extract of Moringa oleifera leaves in three concentrations can decrease expression of HSF1 in oral cancer induced by benzo[a]pyrene.